ANALISIS PERHITUNGAN PAJAK PERTAMBAHAN NILAI (PPN) PADA PT. XYZ - Arfandi .; Muhammad Nur Abdi (Universitas Muhammadiyah Luwuk Banggai, 2023)
Tax revenue is one of the most important sources of financing for national development. Changes in the economic structure from an agricultural economy to an industrial economy have led to an increasing role of taxes, especially VAT, as financing, the objectives of this study are How is the calculation of Value Added Tax at PT XYZ and How is the accounting treatment for the calculation of Value Added Tax at PT XYZ. The research method is a quantitative description with a purposive sampling approach with the condition that the tax provisions of VAT are 11%, the results of the study found that in calculating Value Added Tax (VAT), the indirect method can be used, namely output tax minus input tax, the result obtained is the tax that must be deposited into the State treasury.